Electron-impact coherence parameters for electron-impact excitation of laser-excited 174Yb (. . . 6s6p 3P1) - Hein, J.; Kidwai, S.; Zetner, P.; Bostock, Christopher; Fursa, Dmitry; Bray, Igor; Sharma, L.; Srivastava, R.; Stauffer, A. (Institute of Physics Publishing Ltd., 2011)
We have measured and calculated the P3 collision Stokes parameter for electron-impact collisional de-excitation to the ytterbium (. . . 6s6p 3P1) level from the higher-lying 1P1, 3D1,2,3 and 3S1 levels for 20 eV residual energy. These processes are the time-reverse of the experimentally measured processes, where an impact energy of 20 eV was used to collisionally excite the 3P1 target, prepared by resonant laser pumping. Measurements were performed using a crossed-beam apparatus, where excited-state atomic targets were produced using resonant laser radiation incident on the electron–atom interaction region. Calculations were performed in the relativistic convergent close-coupling , convergent close-coupling and relativistic distorted-wave approximations. The theoretical calculations show that the helectron-impact coherence parameter (EICP) is equal to 1/2, independent of the scattering angle. We use this result to present the L! EICP for the (. . . 6s7s 3S1)-->(. . . 6s6p 3P1) collision process.